Local Actions, National Policies and International Knowledge: Family Planning and Statistical Practices in Taiwan (1949–1980s). (5th February 2019) - Lin, Yi-Tang
Summary: Using an approach based on the sociology of quantification, this article illustrates how actors utilised statistics when importing family planning to Taiwan and exporting their experience to international policy makers. The functions of statistics—producing knowledge and making policies—assisted the implementation of international programmes in Taiwan, where any actions leading to a population decrease were prohibited in the 1950s. The Population Council and Taiwanese officials first secured the provincial government's tacit consent by claiming the programme to be an experiment in general population policy rather than one focused on the insertion of intra-uterine devices (IUDs). They went on to win the central government's endorsement in 1964 by presenting IUD insertions as tools for achieving the ideal population size for economic development. Finally, experts packaged and repackaged the Taiwan programme as a success by wielding locally-collected statistics, reframing the programme to fit the conclusions of international research at the time.